The use of autologous bone grafts and xenogenic bone materials for reconstruction of the facial bone defects (randomized prospective study) - Rybak, V. A.; Pavlychuk, T. A.; Kopchak, A. V. (Journal of Education, Health and Sport, 2018)
The objective - to compare the efficacy of surgical interventions to replace jaw defects with the use of different types of bone grafts based on objective clinical and radiological criteria. The study included 90 patients with postoperative jaws defects. They underwent reconstructive operation for creating conditions for further prosthetic rehabilitation. The patients were divided into 3 randomized groups, depending on the surgical treatment used: group I - xenogenic bone substitutes were used, group II - autologous corticocancellous bone grafts from the iliac crest and in group III autograft combined with PRGF. Patients’ status was assessed in the early (up to 1 month) and long-term postoperative period (more than 6 months). In the study series, xenogenic materials showed the highest volumetric stability in the remote postoperative period (19,9 ± 8,1% versus 45.6 ± 21.84% for bone autografts). However, autologous grafts demonstrated better integration and quality of bone tissue. There were no significant differences in frequency of postoperative complications or the possibility of implant placement in the study groups. The use of PRGF in combination with autograft accelerated the regeneration of soft tissues, but it does not affect significantly the incidence of infection complications and volume loss of the bone grafts.